Enhanced the electrochemical properties of Ni doped V2O5 as a electrode material for supercapacitor applications. (2022) - Uma Shankar, V.; Govindarajan, D.; Christuraj, P.; Salethraj, M. Joseph; Johanson, F. Joy; Raja, M. Dinesh
Abstract: Ni doped V2 O5 nanorods were synthesized by simple sol–gel route. The effect of Ni doping has been studied through XRD, Micro-Raman, SEM and CV analysis. The XRD result shows that the synthesized samples were exhibits orthorhombic structured V2 O5 . SEM images illustrate the Ni particles are decorated on the V2 O5 rod surfaces. From the Raman analysis, the prepared samples are observed in V-O vibrational modes without impurities. Both V2 O5 and Ni:V2 O5 electrodes are exhibits pseudocapacitance nature, which shows the superior specific capacitance values for 112 and 152 Fg −1 at 10 mVs −1, respectively.